The city as a place of production of values - Kudłacz, Michał (Journal of Public Governance, 2017)
For centuries, cities have been centres of dynamic and complex economic, social, and spatial processes. Concentration of potentials has been conducive to development of our civilization, which has resulted in a change of the perception of what is good and valuable. The words: “city” and “value” are inextricably linked since cities are engines of social and economic development, providers of knowledge and innovation, and determinants of cultural development. In this paper the author attempts to analyze the evolution of the concept of values in cities in various periods of history. He then tries to determine the nature of values in cities and establish classifications (types) of values in order to find out whether there are universal values.